2013
DOI: 10.1002/stem.1490
|View full text |Cite
|
Sign up to set email alerts
|

In situ mechanotransduction via vinculin regulates stem cell differentiation

Abstract: Human mesenchymal stem cell (hMSC) proliferation, migration, and differentiation have all been linked to extracellular matrix stiffness, yet the signaling pathway(s) that are necessary for mechanotransduction remain unproven. Vinculin has been implicated as a mechanosensor in vitro, but here we demonstrate its ability to also regulate stem cell behavior, including hMSC differentiation. RNA interference-mediated vinculin knockdown significantly decreased stiffness-induced MyoD, a muscle transcription factor, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 62 publications
7
95
0
Order By: Relevance
“…Most of the molecules discovered to date are cytoskeletal proteins such as myosin II (7), the Rho/ ROCK system (8,10), and vinculin (11). Although cytoskeletal proteins and cellular contractility regulators are essential for generating traction forces and sensing environmental mechanics, the molecular mechanisms connecting these signaling molecules to intracellular pathways that influence differentiation have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the molecules discovered to date are cytoskeletal proteins such as myosin II (7), the Rho/ ROCK system (8,10), and vinculin (11). Although cytoskeletal proteins and cellular contractility regulators are essential for generating traction forces and sensing environmental mechanics, the molecular mechanisms connecting these signaling molecules to intracellular pathways that influence differentiation have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mesenchymal and neural stem cells have revealed the involvement of focal adhesion zones and cytoskeletal proteins, such as integrins, nonmuscle myosin II (7), Rho GTPases (8)(9)(10), and vinculin (11), that participate in the generation of cellular traction forces. Recent work also has identified the nucleoskeletal protein lamin-A (12) and the transcriptional coactivators Yap (Yesassociated protein) and Taz (transcriptional coactivator with PDZbinding motif) (13) in mechanotransduction in mesenchymal stem cells.…”
mentioning
confidence: 99%
“…The conversion of extracellular forces to intracellular signalling events is termed mechanotransduction; focal adhesions (FAs), which link the intracellular actin cytoskeleton to the ECM via integrins, are implicated as mechanosensitive cellular organelles (Puklin-Faucher and Sheetz, 2009;Schwarz and Gardel, 2012), capable of sensing forces and generating signalling events in response (Goldmann, 2012). The FA protein vinculin has been shown to be particularly important for mechanotransduction (Atherton et al, 2016); the link between vinculin and actin is required for cell polarization and Rac1 activation in response to cyclic stretching (Carisey et al, 2013), and vinculin is involved in generating cellular responses to different ECM rigidities (Holle et al, 2013;Rubashkin et al, 2014;Yamashita et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Vinculin-null cells remain capable of performing many of the cellular functions thought to depend on FA force sensing; they form FAs, migrate, and generate adhesive forces. 2,[18][19][20][21] However, the development of more sensitive and quantitative force-sensing assays (on both the cellular and molecular level) has revealed that vinculin-null cells cannot generate as strong of traction forces, 2 they have lower membrane stiffness, 20 and they exhibit abnormal migration behaviorthey migrate faster but with reduced persistence-compared with their vinculinexpressing counterparts, 18 and that vinculin itself can exist within FA in a fully activated, but unstrained state, 11 suggesting a perhaps more nuanced role of vinculin in FA mechanosensing. Indeed, a better understanding how vinculin modulates forces on the cellular level could lead to an improved understanding of vinculin's role in the development and maintenance of tissues and organs that experience and generate mechanical forces, perhaps leading to new drug targets and better treatments for a wide-set of diseases (e.g., chronic cardiac failure).…”
Section: A Helping Handmentioning
confidence: 99%
“…The results contradict the recent findings of Holle, et al, who found that human mesenchymal stem cells with significantly reduced levels of vinculin do not show altered adhesive properties or diminished cell traction force generation, suggesting that the magnitude of vinculin's effect on traction force could be cell type-specific; perhaps because of cell type-specific differences in the organization of the CSK. 21,25 An alternative explanation for this result is that the knockdown of vinculin was not sufficient to fully reduce vinculin levels below a level that altered vinculin function within the cell. Indeed, vinculin function within the cell is governed by its autoinhibitory binding and is unlikely to be altered by high or low levels of total vinculin protein within the cell.…”
Section: Vinculin Regulates But Is Not Required For the Generationmentioning
confidence: 99%